(untitled) (The Research of Medical Science Review, 2025)
Shifting of hosts is a significant factor that directs holoparasitic species’ evolution and development, as well as determines their chances at survival. This work explores the genetic, ecological, and morphological criteria involving host transitions and assesses how such switches affect changes in parasitic-host co-evolution. In this comparative study, we applied multiple holoparasitic species across the different host systems to reveal patterns of evolution alongside ecological constraints on parasitic life. Research data show that different hosts cause pronounced changes in gene properties that either promote niche-specific adaptation or enhance broad host generalism. Such findings are useful for knowing more about parasitic evolution and its impact on the changes in ecosystems.